2020
DOI: 10.21608/ejhc.2020.142683
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Swallowing Training Rehabilitation Program on Severity of Dysphagia and Swallowing Trial among Patients with Cerebrovascular Stroke

Abstract: Background: Cerebrovascular Stroke (CVS) is a rapidly developing clinical focal disorder of cerebral function lasting for 24 hours or longer and leading to death, with no obvious reason other than the vascular source. Aim of the study: was to determine the effect of swallowing training rehabilitation program on severity of dysphagia and swallowing trial among patients with cerebrovascular stroke Research design: A quasi experimental research design with a pretest-posttest control group was utilized. Settings: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…This finding agrees with Banda et al, (2021) who reported that swallowing exercises had significantly better effects on swallowing function in the experimental group compared with the control group, and also, in the same line with Greco et al, (2018). This may be related to as rehabilitation swallowing exercises had a significant positive effect on dysphagia or swallowing difficulties, this view supported by Gomah Yousef El-Deeb & Elsayed Rady, (2020). As swallowing exercises focused on strengthen muscles and enhancing synchronization between the nerves and muscles involved in swallowing, exercising swallowing muscles is the greatest strategy to improve your ability to swallow.…”
Section: Resultssupporting
confidence: 89%
“…This finding agrees with Banda et al, (2021) who reported that swallowing exercises had significantly better effects on swallowing function in the experimental group compared with the control group, and also, in the same line with Greco et al, (2018). This may be related to as rehabilitation swallowing exercises had a significant positive effect on dysphagia or swallowing difficulties, this view supported by Gomah Yousef El-Deeb & Elsayed Rady, (2020). As swallowing exercises focused on strengthen muscles and enhancing synchronization between the nerves and muscles involved in swallowing, exercising swallowing muscles is the greatest strategy to improve your ability to swallow.…”
Section: Resultssupporting
confidence: 89%